Wage Inequality: Its Impact on Customer Satisfaction and Firm Performance - Bamberger, Boas; Homburg, Christian; Wielgos, Dominik M. (Journal of Marketing, 2021)
This article adopts a marketing perspective to examine how wage inequality between top managers and their employees may have customer-related consequences (i.e., customer-directed effort, customer-directed opportunism, and customer-oriented culture) that affect customer satisfaction and firm performance. Surprisingly, marketing scholars and practitioners have largely neglected this pressing societal issue. The authors collect a cross-industry, multisource data set, including responses by top-level managers and objective data on wage inequality and firm performance from 106 business-to-business-focused firms (Study 1). In addition, they analyze multisource longitudinal panel data covering 521 firm-year observations for business-to-consumer-focused firms (Study 2). The results consistently reveal that wage inequality harms customer satisfaction. This relationship is mediated by customer-directed opportunism and customer-oriented culture but not customer-directed effort. Moreover, while wage inequality has a positive direct effect on short-term firm profitability, this effect is dampened by the negative indirect effect through customer-related consequences and customer satisfaction. Importantly, the positive direct effect of wage inequality on short-term profitability vanishes in the long run, whereas the adverse effect through customer satisfaction persists, leading to a nonsignificant total effect on long-term profitability. These findings may guide researchers, managers, shareholders, and policy makers in addressing the challenge of rising wage inequality.